2021
DOI: 10.3390/cells10102579
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Serum Metabolites of Acute Intermittent Porphyria and Asymptomatic HMBS Mutation Carriers

Abstract: This study aims to present the serum metabolite profiles of patients with acute intermittent porphyria (AIP) and identify specific metabolites that could potentially discriminate between AIP, asymptomatic HMBS mutation carriers, and healthy individuals. The study cohort included 46 female participants: 21 AIP patients, 5 asymptomatic carriers, and 20 ‘normal’ participants (without HMBS gene mutation). Serum samples were analyzed for 157 selected metabolites or clinical variables using an assay combining liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Most recently, it emerged that AIP experimental models show impaired glucose metabolism and mitochondrial respiration capacity during acute attacks, while carriers of AIP displayed high body weight, hyperinsulinemia, and alterations in serum lipid profiles combined with IR [16,38,39]. These findings suggest that AIP may be considered a genetic disorder characterized by an umbrella of metabolic dysfunctions, thereby adding new additional knowledge about its pathophysiology and, possibly, novel curative strategies.…”
Section: Heme Biosynthesis and Aip Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, it emerged that AIP experimental models show impaired glucose metabolism and mitochondrial respiration capacity during acute attacks, while carriers of AIP displayed high body weight, hyperinsulinemia, and alterations in serum lipid profiles combined with IR [16,38,39]. These findings suggest that AIP may be considered a genetic disorder characterized by an umbrella of metabolic dysfunctions, thereby adding new additional knowledge about its pathophysiology and, possibly, novel curative strategies.…”
Section: Heme Biosynthesis and Aip Pathogenesismentioning
confidence: 99%
“…Several studies underlined that caloric impoverishment exasperates acute attacks of AIP and many individuals with AIP with severe symptomatology maintain an inadequate carbohydrate intake, suggesting that dietary carbohydrates or glucose infusions may be supplemented to reduce the severity of these events [38][39][40][41][42]. Matkovic and colleagues demonstrated that the hormonal regulation of carbohydrates may be modeled by porphyrinogenic drugs such as 2-allyl-2-isopropylacetamide (AIA) and 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC).…”
Section: Impaired Glucose Homeostasis and Ir Contribute To Acute Atta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol, smoking, drugs, fasting/hunger, and changes in women's sex hormone levels are the common precipitants (1,9). Differences have been found in the serum metabolic profiles between normal individuals and patients carrying the HMBS variant (10). All individuals with pathogenic HMBS gene variants are at risk of developing acute attacks, and chronic complications such as hepatocellular carcinoma, hypertension, and chronic renal failure can occur in both symptomatic AIP and latent patients with pathogenic HMBS variants (8,11).…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of the genome in combination with the metabolome alterations produced by AIP might shed light on these mechanisms [ 9 , 10 , 11 ]. Several metabolic alterations produced by AIP have been previously reported [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. For instance, steroids are incriminated in the induction of porphyria [ 19 ] and our group reported that AIP alterations in the urinary steroidome are correlated with ALA concentration [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%